A scientometric review of the synergetic effects of emotions on the travel motivation of senior tourists - Pestana, M.; Moutinho, L.; Philips, P. (Proceedings of the TMS Algarve 2016 – Tourism & Management Studies International Conference, 2016)
This paper seeks to make three contributions to the senior tourism literature. The first apllies a scientometric review to analyse when, how and why the subject title has potential value in scientific domain; the second measure and validate senior tourists’ emotional experiences when vacationing in Lisbon, adapting Hosany and Gilbert Destination Emotion Scale (DES); and the third identifies the effect of positive emotions on push motivations. The scientometric review over 18479 bibliographical records published since 1900, were retrieved by terms from the Web-of-Science and exported to CiteSpace. A sample of 464 senior tourists vacationing in Lisbon was conducted to analyses the synergetic effect of emotions on the travel motivations of senior tourists, applying structural equations modeling (SEM). The results shows the association between positive emotions, place attachment and push motivations in seniors tourist experience, through the connection between ten areas of research in the knowledge domain: the first seven major clusters (#0 to #6), and three small clusters: #10 with the reference Jang, (2009); # 41, with the reference Sangpikul, (2008) and cluster #48 with the reference Pearce, (2005).